Tasawuf sebagai Landasan Pendidikan Karakter: Membangun Integritas dan Ketahanan Mental Generasi Muda - Zulkifli Zulkifli; M. Hidayat (CV. ALIM'SPUBLISHING, 2026)
This article examines Sufism as a foundation for character education in building the integrity and mental resilience of the younger generation amidst the challenges of modernity, globalization, and digital culture. The main issue raised is the weak internalization of values ​​in character education, which has tended to stop at the normative, ceremonial, and cognitive levels. Using a qualitative approach based on literature study, this article analyzes classical and contemporary literature on Sufism, character education, Islamic spirituality, resilience, and students' mental health. The results of the study indicate that Sufism has strong relevance because it offers a framework for soul training through tazkiyat al-nafs, muhasabah, muraqabah, control of desires, and moral habits. Sufi values ​​such as sidq, amanah, sabr, ikhlas, tawadhu, and zuhud can be translated into indicators of character education, including academic honesty, responsibility, self-control, social empathy, discipline, and the ability to handle psychological stress. This article also emphasizes that Sufism should not be understood as an esoteric practice separate from social reality, but rather as a pedagogical paradigm that can be integrated into the curriculum, institutional culture, teacher-student relationships, digital etiquette, and multimodal evaluation. The article's primary contribution is the formulation of the TIR Model: Tazkiyah, Integrity, Resilience, as a conceptual and operational design for Sufism-based character education. This model positions inner training as the foundation for students' moral integrity and mental resilience through the stages of problem diagnosis, core value selection, practice design, mentoring, assessment, and program reflection. Thus, this article offers a more in-depth, systemic, and transformative direction for character education, while also being relevant for Islamic educational institutions addressing the moral crisis and psychological fragility of the younger generation. However, this model still requires empirical testing through field research.